Entreleadership : 20 years of practical business wisdom from the trenches - Ramsey, Dave (New York : Howard Books, 2011)
Offers advice on growing a business, including setting and attaining goals, time management, and operating debt free.
EntreLeadership defined -- Start with a dream, end with a goal : living your dreams, visions, mission statements, and goals -- Flavor your day with steak sauce : making the most of time management and organization --'Spineless leader' is an oxymoron : the easier way to make hard decisions -- No magic, no mystery : the System, the recipe, and the truth about great marketing -- Don't flop whoppers : a practical guide to launching your dream -- Business is easy ... until people get involved : hiring, firing, and personality styles -- Death of a salesman : the art of selling by serving -- Financial peace for business : bulletproof principles for money, debt, and funding your future -- The map to the party : grasping the undeniable relationship between great communication and great companies -- People matter most : building unity and loyalty with your best resource -- Caught in the act : amplifying the success of your business through recognition and inspiration -- Three things successful people never skip : dealing with contracts, vendors, and collections -- Show me the money! : compensation plans that fire people up -- Mastering'the rope' : delegation, the best way to build a business bigger than you.
Includes bibliographical references.
Keywords: Entrepreneurship; Leadership; Executive ability; Success in business